PROFIL RUMAH TANGGA MASYARAKAT PESISIR DI KAWASAN TAMAN NASIONAL PERAIRAN LAUT SAWU - Alexander S. Tanody; Ida Ayu Lochana Dewi (Politeknik Pertanian Negeri Kupang, 2016)
Savu Sea Marine National Park (SSMNP) was declared by Ministry of Marine Affairs and Fisheries (MMAF) of the Republic of Indonesia, on 2014 with total area more than 3.35 Million Ha, which considered as the largest marine national park in the coral triangle region. The management unit and related key stakeholders has developed the programsÂ to measure the level of effective management of SSMNP, which one of the criteria of the effectiveness will be shown from how the park can contribute to the economic benefit of the coastal community inside and surrounding the park. One important aspect as baseline for SSMNP program development is coastal community profile. This assessment was held on July â€“ December 2015 using MMAF tool regarding coastal community perception for MPA development. The study results shown that houses of coastal communities in Savu Sea MNP constructed of cement/brick (52.30%), but the majority (42.82%) are still without electricity. Most households (90.52%) have no fresh water facilities. Means of communication used are mobile phone, television and radio. In generally, they used a canoe to support seaweed farming and fishing in coastal areas. The main livelihoods is farming, seaweed cultivation, self-employed and employees. Household income varies widely, between IDR. 250,000 to IDR 5,000,000 per month for primary income. Most people declared their income dependent on agricultural activity or fishing season.Key word : Conservation, Savu Sea, Marine National Park, coastal community.